Impact of Islamic Motives, Customer Profitability and Service Quality on Customer Satisfaction from Islamic Banks - ARSHAD KHAN; SAYYAM; ABDUR RAHMAN (Journal of Business & Tourism, 2021)
Success of any Islamic banks greatly depends on consumers, so Islamic banks need to create ethical environment, where perception of Islamic banks are carefully developed. The persistence of this is explained the nature and pervasiveness of Islamic banking and to pinpoint the linkage between consumer’s satisfaction and banks performance in Pakistani Islamic banks. And also make out that customer preferred Islamic banks. Islamic banks sector was selected for the research, In order to obtain the required objectives, From Meezan bank and Bank Islami, Nowshera we selected 137customer’s, and data was collected from them through a well-designed questionnaire. SPSS (17.0) were used for analyze togetherthe data. The Cranach’s Alpha () Reliability methods were used to test the reliability of data. Findings exposed that there was significant and up relationship of ISLAMIC banks performance with customer’s satisfaction. So Islamic bank is strong predictor of customer’s fulfillment and determination of C’S depends upon on the Islamic banks performance of relationship.